Policy, Institutional Factors and Earnings Mobility - Denisa Maria Sologon; Cathal O'Donoghue (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper uses ECHP and OECD data for 14 EU countries to explore the role of labour market factors in explaining cross-national differences in the dynamic structure of earnings: in permanent inequality, transitory inequality and earnings mobility. Based on ECHP, minimum distance estimator is used to decompose earnings inequality into the permanent and transitory components and compute earnings mobility. The predicted components together with the institutional OECD data are used in a non-linear least squares setting to estimate the relationship between permanent inequality, transitory inequality and earnings mobility, and labour market policy and institutional factors. The results revealed a highly complex framework, where institutions interact significantly not only with each other and with the overall institutional setting, but also with the macroeconomic shocks in shaping the pattern of the three labour market outcomes.
Keywords: C23; D31; J31; J60; J50; J8; 330; Panel data; wage distribution; inequality; mobility; labour market institutions; labour market policies